An optimized ship hull fitting approach using nurbs - Ang, Swee Wen; Shamsuddin, Siti Mariyam; Samian, Yahya (2006)
Ship hull form module is the main module in ship design. The problem of creating fair ship hull surface is of major importance in Computer Aided Ship Design environment. The fitness of these surfaces is generally considered a subjective notion depending on the judgment of the designers (eg. visually pleasing, devoid of unnecessary bumps or wiggles, satisfying certain continuity requirements). One of the restriction in ship hull design is that the existing details of a ship design on paper or a ship that already been constructed physically couldn’t be reconstructed accurately and concisely in a ship hull design software. This problem can take on many different characteristics, depending on the goal of the reconstruction, the origin of the offset, and tools or methods available to tackle the job. All of these must be taken into account in developing the best approach to solving the problem in the most efficient manner. In the field of surface modeling of hull form, geometric complexity of hull form gives many difficulties. This leads to the issue of what is the best surface reconstruction method for ship hull? This research strives to solve this problem by creating fair ship hull surface using NURBS. An optimized ship hull fitting approach using NURBS is developed. Evaluation and analysis (percentage of accuracy, fairness and speed of processing) on the proposed approach and also comparison of proposed approach and other systems/softwares will be done.